DEVELOPMENT OF ROMANIAN SEASIDE TOURISM IN THE FRAME OF SUSTAINABLE EUROPEAN SOCIETY - GRAŢIELA BRÂNZĂ (Annals of the University of Petrosani: Economics)
Sustainable development can be achieved only in the frame of a sustainable society. In the context of Romania's integration into the Great Society of the European Union, tourism activity should be developed, respecting sustainable tourism principles promoted by the Union. This paper presents statistical analysis of the Romanian seaside tourism and the results of a statistical survey conducted in the summer of 2007 to findout possible means to increase the quality of tourism services on the Romanian seaside. Also, the paper proposes solutions for sustainable tourism development in the Romanian Black Seaarea.